Phase transitions in Fe3Al-based alloys: ab initio study. (2nd January 2020) - Zagrebin, M. A.; Matyunina, M. V.; Miroshkina, O. N.; Pavlukhina, O. O.; Sokolovskiy, V. V.; Buchelnikov, V. D.
ABSTRACT: In this work, based on structural and magnetic phase transition temperatures estimated theoretically from the first principles, the concentration phase diagram for Fe 100 − x Al x ( 15.625 ≤ x ≤ 31.25 at.%) was plotted. Structural phase transition temperatures for the experimentally observed crystal structures were obtained from the structural optimization. It is shown that for x  = 28.125 at.% L1 2 -like phase with slight distortions is energetically favorable. The ground state energy and magnetic moments of Fe 75 Al 25 with different structures were calculated within GGA and GGA+ U approaches. It is shown that in the case of GGA+ U approximation, L1 2 phase becomes more stable compared with D0 3 . The Curie temperatures were estimated from mean field approximation and Monte Carlo simulations using ab initio calculated exchange coupling constants. Both structural and magnetic phase transition temperatures are found in qualitative agreement with the experiment. Depending on Al concentration, five different sequences of phase transitions are observed in the phase diagram.